Weight loss for overweight and obese patients with prostate cancer: a study protocol of a randomised trial comparing clinic-based versus Telehealth delivered EXercise and nutrition intervention (the TelEX trial). Issue 6 (6th June 2022) - Galvão, Daniel A; Taaffe, Dennis R; Hayne, Dickon; Lopez, Pedro; Lyons-Wall, P; Tang, Colin I; Chambers, Suzanne K; Devine, Amanda; Spry, Nigel; Jeffery, Emily; Kudiarasu, Christine; Joseph, David; et al.
Abstract : Introduction: Obese men with prostate cancer have an increased risk of biochemical recurrence, metastatic disease and mortality. For those undergoing androgen deprivation therapy (ADT), substantial increases in fat mass are observed in the first year of treatment. Recently, we showed that a targeted supervised clinic-based exercise and nutrition intervention can result in a substantial reduction in fat mass with muscle mass preserved in ADT-treated patients. However, the intervention needs to be accessible to all patients and not just those who can access a supervised clinic-based programme. The purpose of this study was to evaluate the efficacy of telehealth delivered compared with supervised clinic-based delivered exercise and nutrition intervention in overweight/obese patients with prostate cancer. Methods and analysis: A single-blinded, two-arm parallel group, non-inferiority randomised trial will be undertaken with 104 overweight/obese men with prostate cancer (body fat percentage ≥25%) randomly allocated in a ratio of 1:1 to a telehealth-delivered, virtually supervised exercise and nutrition programme or a clinic-based, face-to-face supervised exercise and nutrition programme. Exercise will consist of supervised resistance and aerobic exercise performed three times a week plus additional self-directed aerobic exercise performed 4 days/week for the first 6 months. Thereafter, for months 7–12, the programmes will be self-managed. The primary endpoint will be fat mass. Secondary endpoints include lean mass and abdominal aortic calcification, anthropometric measures and blood pressure assessment, objective measures of physical function and physical activity levels, patient-reported outcomes and blood markers. Measurements will be undertaken at baseline, 6 months (post intervention), and at 12 months of follow-up. Data will be analysed using intention-to-treat and per protocol approaches. Ethics and dissemination: Ethics approval has been obtained from the Edith Cowan University Human Research Ethics Committee (ID: 2021–02157-GALVAO). Outcomes from the study will be published in academic journals and presented in scientific and consumer meetings. Trial registration number: ACTRN12621001312831.